Strongyloides stercoralis and HTLV-1 coinfection in CD34+ cord blood stem cell humanized mice: Alteration of cytokine responses and enhancement of larval growth. - Lauren E Springer (Public Library of Science (PLoS), 2021)
Viral and parasitic coinfections are known to lead to both enhanced disease progression and altered disease states. HTLV-1 and Strongyloides stercoralis are co-endemic throughout much of their worldwide ranges resulting in a significant incidence of coinfection. Independently, HTLV-1 induces a Th1 response and S. stercoralis infection induces a Th2 response. However, coinfection with the two pathogens has been associated with the development of S. stercoralis hyperinfection and an alteration of the Th1/Th2 balance. In this study, a model of HTLV-1 and S. stercoralis coinfection in CD34+ umbilical cord blood hematopoietic stem cell engrafted humanized mice was established. An increased level of mortality was observed in the HTLV-1 and coinfected animals when compared to the S. stercoralis infected group. The mortality was not correlated with proviral loads or total viral RNA. Analysis of cytokine profiles showed a distinct shift towards Th1 responses in HTLV-1 infected animals, a shift towards Th2 cytokines in S. stercoralis infected animals and elevated TNF-α responses in coinfected animals. HTLV-1 infected and coinfection groups showed a significant, yet non-clonal expansion of the CD4+CD25+ T-cell population. Numbers of worms in the coinfection group did not differ from those of the S. stercoralis infected group and no autoinfective larvae were found. However, infective larvae recovered from the coinfection group showed an enhancement in growth, as was seen in mice with S. stercoralis hyperinfection caused by treatment with steroids. Humanized mice coinfected with S. stercoralis and HTLV-1 demonstrate features associated with human infection with these pathogens and provide a unique opportunity to study the interaction between these two infections in vivo in the context of human immune cells.